2013
DOI: 10.1186/1472-6963-13-525
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in rheumatic fever and rheumatic heart disease management and prevention using a health centre-based continuous quality improvement approach

Abstract: BackgroundRheumatic heart disease (RHD) remains a major health concern for Aboriginal Australians. A key component of RHD control is prevention of recurrent acute rheumatic fever (ARF) using long-term secondary prophylaxis with intramuscular benzathine penicillin (BPG). This is the most important and cost-effective step in RHD control. However, there are significant challenges to effective implementation of secondary prophylaxis programs. This project aimed to increase understanding and improve quality of RHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…Challenges to delivery of this regimen in remote Australian settings are similar to those in many resource‐poor populations globally with the highest RHD burdens: high turnover and limited ARF knowledge among healthcare staff; young and mobile patients; pain of injections; and cultural factors leading to different concepts of disease causation and treatment, along with barriers to acceptance of Western medicine 8, 9, 10. The proportion of patients in the NT in 2009 with ARF/RHD achieving ≥80% of scheduled injections—the current Australian benchmark for acceptable adherence7—was only ≈25% 11…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Challenges to delivery of this regimen in remote Australian settings are similar to those in many resource‐poor populations globally with the highest RHD burdens: high turnover and limited ARF knowledge among healthcare staff; young and mobile patients; pain of injections; and cultural factors leading to different concepts of disease causation and treatment, along with barriers to acceptance of Western medicine 8, 9, 10. The proportion of patients in the NT in 2009 with ARF/RHD achieving ≥80% of scheduled injections—the current Australian benchmark for acceptable adherence7—was only ≈25% 11…”
Section: Introductionmentioning
confidence: 89%
“…CQI approaches use data proactively to motivate healthcare providers and clinic managers to work toward improved targets. Application of CQI has shown promise previously in the NT, with implementation at 6 remote clinics leading to improvements in some ARF/RHD outcomes 11. Health systems improvements providing a “comprehensive care program” or combining education strategies with development of a register have also been associated with ARF rate reductions in the United States, Cuba, and the Caribbean 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…One study from the Northern Territory in Australia suggested that CQI activities did improve some aspects of ARF/RHD care but had no impact on the proportion of patients receiving ≥80% of their scheduled LAB injections. 41 Thus, it remains unclear whether formal CQI initiatives are superior to other organizational strategies to improve service delivery such as those that encourage reflective and responsive health care at an individual provider level.…”
Section: Health Care Organizationmentioning
confidence: 99%
“…CQI processes aim to engage staff in understanding and responding to their own data and can be a powerful tool to motivate change in primary care settings 10. We previously showed incremental improvements in clinical care targets achieved in RHD management using CQI 2. Processes included proactive use of adherence data from each participating clinic to motivate healthcare providers and managers to work toward improved penicillin delivery targets, specifically, for more clients to achieve ≥80% of scheduled injections.…”
Section: Methodsmentioning
confidence: 99%